2013
DOI: 10.1089/vim.2012.0052
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Immunization Elicits Polyomavirus-Specific MHC Class Ib-Restricted CD8 T Cells in MHC Class Ia Allogeneic Mice

Abstract: Unlike the polymorphic MHC class Ia molecules, MHC class Ib molecules are oligomorphic or nonpolymorphic. We recently discovered a protective CD8 T cell response to mouse polyomavirus (MPyV) in H-2 b haplotype mice that is restricted by H2-Q9, a member of the Qa-2 MHC class Ib family. Here, we demonstrate that immunization with a peptide corresponding to a virus capsid-derived peptide presented by Q9 also elicits MHC class Ibrestricted MPyV-specific CD8 T cells in mice of H-2 s and H-2 g7 strains. These findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…However, Q9-restricted T cells are somewhat different from classical CD8 + T cells because they form an inflationary population during persistent infection for approximately 12 weeks (Swanson et al 2008). Further characterization showed that immunization with a VP2.139 peptide in mice carrying different MHC haplotypes could generate an MPyV-specific non-classical CD8 + T cell response (Hofstetter et al 2013). However, the authors were not able to determine whether this population provided enhanced control during MPyV infection (Hofstetter et al 2013).…”
Section: Mhc Class Ib-restricted Cd8+ T Cells and Their Participatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Q9-restricted T cells are somewhat different from classical CD8 + T cells because they form an inflationary population during persistent infection for approximately 12 weeks (Swanson et al 2008). Further characterization showed that immunization with a VP2.139 peptide in mice carrying different MHC haplotypes could generate an MPyV-specific non-classical CD8 + T cell response (Hofstetter et al 2013). However, the authors were not able to determine whether this population provided enhanced control during MPyV infection (Hofstetter et al 2013).…”
Section: Mhc Class Ib-restricted Cd8+ T Cells and Their Participatmentioning
confidence: 99%
“…Further characterization showed that immunization with a VP2.139 peptide in mice carrying different MHC haplotypes could generate an MPyV-specific non-classical CD8 + T cell response (Hofstetter et al 2013). However, the authors were not able to determine whether this population provided enhanced control during MPyV infection (Hofstetter et al 2013). …”
Section: Mhc Class Ib-restricted Cd8+ T Cells and Their Participatmentioning
confidence: 99%